Use of Interferon‐γ release assay for the diagnosis of female genital tuberculosis in Northwest China. Issue 1 (13th July 2018) - Lu, Xi; Li, Chunmeng; Li, Wangping; Long, Xiaoheng; Fang, Yanfeng; Sun, Ruilin; Jin, Faguang; Fu, Enqing; Xie, Yonghong
Abstract : Background: Female genital tuberculosis (FGTB) is one of the major causes of infertility. However, nonspecific manifestations and the lack of easy access to gold‐standard diagnostic test render a diagnostic difficult for FGTB. The objective of this study was to determine T‐SPOT.TB (an interferon‐γ release assay, IGRA) performance in patients with FGTB. Methods: A total of 213 female patients with validated T‐SPOT.TB results were recruited in this retrospective study. Among which, 103 were confirmed FGTB, and 110 were excluded from tuberculosis (control). Of the confirmed FGTB patients, 52 were confirmed by microbiologically/histopathologically examination, while the remaining 51 were clinically confirmed (successfully responsive to anti‐tuberculosis treatment). T‐SPOT.TB test was performed in both FGTB and control group during the diagnostic procedure. Results: The overall sensitivity and specificity of T‐SPOT.TB were 86.41% and 75.45% respectively. Sensitivity of T‐SPOT.TB was significantly higher when compared with conventional tuberculosis diagnostic tests. Moreover, T‐SPOT.TB test using pelvic effusion (PE) showed higher sensitivity than using corresponding peripheral blood (PB) (94.44% vs 72.22%, P < 0.001). Mean value of spot forming cells (SFCs) of T‐SPOT.TB using PE was significantly higher than that of PB in FGTB group (193 (IQR 105‐280) SFCs/2.5 × 10 5 PEMCs vs 71 (IQR 36‐107) SFCs/2.5 × 10 5 PBMCs, P = 0.01), while this was not detected in control group (11 (IQR 0‐22) SFCs/2.5 × 10 5 PEMCs vs 9 (IQR 0‐18) SFCs/2.5 × 10 5 PBMCs, P = 0.77). Conclusion: These results demonstrated that T‐SPOT.TB, especially PE T‐SPOT.TB, is an useful adjunct in FGTB diagnosis.